Yahoo Web Search

  1. Ad
    related to: R
  1. 0.2 + r = 0.2r − 0.06 + 0.3r Fist, let's simplify the right side side: r + 0.2 = 0.5r − 0.06 Next, isolate r and simplify. ( r + 0.2) - 0.5r - 0.2...

    12 Answers · Science & Mathematics · 16/10/2007

  2. r - 2s = 14 Solve for s: Subtract r off both sides: -2s = 14 - r Multiply both sides by -1 to avoid trouble later: 2s = r - 14 Divide by 2: s = ( r - 14)/2

    5 Answers · Science & Mathematics · 21/09/2012

  3. r = (0.001 * t^4 - 4t + 100)^(1/2) r ^2 = 0.001 * t^4 - 4t + 100 2r * dr/dt = 0.001 * 4 * t^3 - 4 dr/dt...004 * t^3 - 4 4 = 0.004 * t^3 4 / 0.004 = t^3 1000 = t^3 10 = t r ^2 = 0.001 * t^4 - 4t + 100 r ^2 = 0.001 * 10000 - 4 * 10 + 100 r ^2...

    3 Answers · Science & Mathematics · 23/12/2015

  4. r - 5 = 6.2 r = 6.2 + 5 r = 11.2

    6 Answers · Science & Mathematics · 07/11/2010

  5. lim ((a^ r + b^ r )/2)^(1/ r ) (as r --> 0) LN lim = lim LN lim LN ((a^ r + b^ r )/2)^(1/ r ) = = lim (1/ r )LN ((a^ r + b^ r )/2) (as r --> 0) is...

    3 Answers · Science & Mathematics · 15/10/2012

  6. The answer is r = -.5 I didn't know if you wanted the explanation or not but I...: 2r=-1 Divide 2r by both sides and the answer is r =-1/2 or -.5

    2 Answers · Science & Mathematics · 14/10/2010

  7. Since r ^2 = (- r )^2, we can assume without loss of generality that r ≥ 0. For each fixed r ≥ 0, A( r ) is a circle centered at (0, 0) with radius r . (When r = 0, then A(0) is simply {(0, 0)}.) Hence...

    1 Answers · Science & Mathematics · 27/03/2012

  8. I = (2V/ R ) + 2r I - (2V/ R ) = 2r r = (1/2) * [I - (2V/ R ... - IR r = (2V - IR) / 2I r = (V/I) - ( R /2)

    3 Answers · Science & Mathematics · 16/01/2014

  9. R is an equivalence relation on R² follows from the fact that equality is an equivalence relation on R¹. (a; b) R (a; b) since a=a, so R is reflexive if (a; b) R (c; d) then...

    2 Answers · Science & Mathematics · 20/10/2012

  10. An ideal in r is a subset I of r such that, for any element x in r and any element i...become easier to check. For (a), if we take any function y(x) from r and any function z(x) from the proposed subset, we see that for x = 1, z(x...

    1 Answers · Science & Mathematics · 05/03/2012

  1. Try asking your question on Yahoo Answers